Active species transfer-type artificial light harvesting system in the nanosheet – Dye complexes: Utilization of longer wavelength region of sunlight. Issue 6 (7th February 2018) - Suzuki, Shunpei; Tatsumi, Daichi; Tsukamoto, Takamasa; Honna, Ryou; Shimada, Tetsuya; Inoue, Haruo; Takagi, Shinsuke
Graphical abstract: Highlights: Ga phthalocyanine and Ru porphyrin co-adsorbed system on the nanosheet was prepared. Ga phthalocyanine absorbs light at longer wavelength region than Ru porphyrin. Ru porphyrin + was produced despite Ga phthalocyanine was irradiated. Active species transfer-type artificial light harvesting system on clay was proposed. Abstract: A novel light harvesting system that captures long-wavelength light of sunlight by the use of hole transfer was newly investigated. Ga phthalocyanine(Ga III TMAPc 4+ (D)) and Ru porphyrin(Ru II DMPyMP 2+ (A)) co-adsorbed reaction system on the synthetic nanosheet was examined as an artificial light harvesting system. By irradiating 660 nm light, where Ga III TMAPc 4+ (D) absorbs, to the system under a presence of PtCl6 2− as an electron acceptor, cation radical of Ru II DMPyMP 2+ (A) was produced despite that Ru porphyrin adsorbs only 413 and 533 nm light. The efficient hole transfer reaction from Ga III TMAPc 4+ (D) +, that is generated from its excited state, to Ru II DMPyMP 2+ (A) takes place on the nanosheet.